Correlation of isokinetic and novel hand-held dynamometry measures of knee flexion and extension strength testing - Whiteley, R.; Jacobsen, P.; Prior, S.; Skazalski, C.; Otten, R.; Johnson, A. (Journal of Science and Medicine in Sport, 2012)
Objectives: Describe inter-rater reliability of, and correlations between a novel method of isometric knee extension and flexion and eccentric knee flexion strength using hand-held dynamometry and isokinetic testing for flexion/extension in the knees of athletic participants. Document strength data normalized to the individual`s limb muscle mass. Design: Observational and reliability study. Methods: Inter-rater reliability for each of the hand-held dynamometry measures was established in both legs of 10 volunteers (6 male). During routine annual screening, 216 male professional football (soccer) players were examined using these same measures in addition to performing an isokinetic evaluation of knee flexion and extension strength. Intra-class correlation coefficients for inter-rater reliability, Pearson r correlations between hand-held dynamometry and isokinetic dynamometry were calculated. Peak torque, peak torque normalized to: body weight; lean body mass; and lean limb mass were documented. Results: Excellent inter-rater reliability was demonstrated with intra-class correlation(2,1) values of 0.90, 0.91, and 0.96, for the eccentric hamstrings, isometric hamstrings, and isometric quadriceps measures respectively. Medium to high correlations (r = 0.322-0.617) which were all significant (p < 0.001) were found for the comparisons between the hand-held dynamometry and isokinetic measures. Conclusions: We present 3 novel and reliable methods of examining knee flexion and extension strength using hand-held dynamometry which require less skill and strength on the part of the examiner than previous measures. Correlations between these measures and isokinetic dynamometry are documented. The hand-held dynamometry examinations took less than 4 min per player to conduct and may be useful in clinical practice where isokinetic examination can be difficult to implement.